2020
DOI: 10.1007/s11482-020-09814-5
|View full text |Cite
|
Sign up to set email alerts
|

Correction to: Decent Work and Work Engagement: A Profile Study with Academic Personnel

Abstract: written by Graça, Pais, Mónico, dos Santos, Ferraro, & Berger, in Table 1, the likert''options-of-response of dimensions 'Dedication' and 'Absorption' begin at '0' (zero) not 1. Unfortunately, it appears as 1 in the first version of publication. All the Likert'option-of-response in this instrument (the UWES) variate among '0'' (zero) and '6' (six).The original article has been corrected.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Since teachers experience a great deal of stress during the course of their careers, teaching has long been considered a high-stress occupation ( Johnson et al, 2005 ; Noor and Zainuddin, 2011 ; Liu and Cheung, 2015 ). For academic personnel, stressors include high pressure to publish and task-role balance management put extra burden on their shoulders ( Graça et al, 2020 ). This situation can be even harsher for Chinese university teachers due to the ambition of building more world-class universities ( Zhu et al, 2018 ; Zhang et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Since teachers experience a great deal of stress during the course of their careers, teaching has long been considered a high-stress occupation ( Johnson et al, 2005 ; Noor and Zainuddin, 2011 ; Liu and Cheung, 2015 ). For academic personnel, stressors include high pressure to publish and task-role balance management put extra burden on their shoulders ( Graça et al, 2020 ). This situation can be even harsher for Chinese university teachers due to the ambition of building more world-class universities ( Zhu et al, 2018 ; Zhang et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the mediating variable, only one hypothesis demonstrated full mediation (Graça et al, 2021). In Hypothesis 7, it was revealed that job satisfaction fully mediated the relationship between competency variables and employee involvement.…”
Section: Discussionmentioning
confidence: 92%